DAYA TERIMA SNACK BAR (CHIA SEED DAN KACANG MERAH) PADA PASIEN DIABETES MELLITUS TIPE 2 - Carine Chandra; Dewanta Facrureza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Type 2 Diabetes Mellitus is a chronic metabolic disease with an increasing prevalence in Indonesia. One important strategy in managing this condition is dietary regulation, including the selection of healthy snacks with a low glycemic index, high fiber content, and good nutritional value. Chia seeds and red beans contain fiber, protein, and bioactive compounds that may help maintain blood glucose stability. This study aimed to determine the acceptability of snack bars made from chia seeds and red beans among patients with Type 2 Diabetes Mellitus based on color, aroma, taste, texture, and overall preference. This study employed an experimental method with a descriptive quantitative approach. The snack bars were prepared in three formulations: sample 217 (70% chia seeds and 30% red beans), sample 777 (50% chia seeds and 50% red beans), and sample 824 (30% chia seeds and 70% red beans). Organoleptic and hedonic tests were conducted on 30 untrained panelists diagnosed with Type 2 Diabetes Mellitus using a 1–5 preference scale. Data were analyzed using the Friedman test. The results showed significant differences in panelists’ preference levels among the three formulations (p<0.05). Samples 217 and 777 showed high mean scores in several sensory aspects. Sample 777 obtained mean scores of 4.90 for color, 4,07 for aroma, 4,27 for taste, 4,43 for texture, and 4,47 for overall preference, making it the most accepted formulation overall. Therefore, snack bars made from chia seeds and red beans have the potential to be developed as healthy snack alternatives for patients with Type 2 Diabetes Mellitus.